Long‐term outcome of percutaneous intervention for pulmonary vein stenosis after pulmonary vein isolation procedure. Issue 3 (28th November 2019) - Suntharos, Patcharapong; Worley, Sarah E.; Liu, Wei; Siperstein, Marion; Prieto, Lourdes R.
Abstract: Objectives: Report long‐term outcomes of percutaneous intervention in patients with pulmonary vein stenosis (PVS) after pulmonary vein isolation (PVI) from a single center over 16 years. Background: Outcome reports of percutaneous intervention for PVS resulting from PVI are limited. Methods: Retrospective review of all patients with PVS after PVI who underwent percutaneous intervention at the Cleveland Clinic Foundation between January 2000 and December 2016. Results: A total of 205 patients underwent cardiac catheterization for PVS during the study period. Completely occluded veins which could not be recanalized occurred in six patients. Of the remaining 199 patients, 27 (14%) were lost to follow‐up, leaving 172 patients with 276 veins for analysis. Balloon angioplasty was performed in 62 veins and stent implantation in 250 (primary in 214, to treat postdilation restenosis in 36). Re‐intervention occurred in 45/62 (73%) balloon‐dilated veins and 45/250 (18%) stented veins. Freedom from re‐intervention at 1 and 5 years was 90 and 73% following stenting versus 40 and 23% following balloon dilation ( p < .001, Hazard ratio (HR) = 5.7). Veins with stent diameter ≥7 mm ( n = 231) had greater freedom from re‐intervention (95% at 1 year, 79% at 5 years) than veins with stents <7 mm (43% at 1 year, 9% at 5 years), p < .001. There was clear symptomatic improvement after intervention and no procedural mortality. Conclusions: Stent implantation at ≥7 mm for PVS after PVI is associated with low rates of re‐intervention, in contrast to balloon dilation and stenting with small conventional stents.